1997
DOI: 10.1128/mcb.17.3.1441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mutant Cell Line That Does Not Activate NF-κB in Response to Multiple Stimuli

Abstract: Numerous genes required during the immune or inflammation response as well as the adhesion process are regulated by nuclear factor B (NF-B). Associated with its inhibitor, IB, NF-B resides as an inactive form in the cytoplasm. Upon stimulation by various agents, IB is proteolyzed and NF-B translocates to the nucleus, where it activates its target genes. The transduction pathways that lead to IB inactivation remain poorly understood. In this study, we have characterized a cellular mutant, the 70/Z3-derived 1.3E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 60 publications
6
52
0
Order By: Relevance
“…Stable and Transient Transfections-The 1.3E2 cells were transiently transfected essentially as in a previous study (26). To generate stable 1.3E2 clones, 5 g of HA-nemo or HA-LZ-mut-nemo plasmids were added to 5 ϫ 10 6 cells in a 500-l volume and electroporated at 260 V, 1500 microfarads, and R ϱ. G418 (1 g/ml) was added the following day, and cells were cloned by limited dilution after a week of selection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable and Transient Transfections-The 1.3E2 cells were transiently transfected essentially as in a previous study (26). To generate stable 1.3E2 clones, 5 g of HA-nemo or HA-LZ-mut-nemo plasmids were added to 5 ϫ 10 6 cells in a 500-l volume and electroporated at 260 V, 1500 microfarads, and R ϱ. G418 (1 g/ml) was added the following day, and cells were cloned by limited dilution after a week of selection.…”
Section: Methodsmentioning
confidence: 99%
“…The murine pre-B cell mutant 1.3E2 not expressing NEMO does not respond to LPS activation (6,26). These cells were transiently co-transfected with an NF-B-dependent construct (Ig -luciferase) and plasmids bearing wild-type or mutant nemo cDNAs.…”
Section: Both the Cc2 And Lz Domains Are Essential To Restore Lps-indmentioning
confidence: 99%
“…The human retinoblastoma cell line Y79 (American Type Culture Collection; Manassas, VA), was grown in RPMI 1640 medium supplemented with 100 units/ml penicillin, 100 g/ml streptomycin, and 10% fetal calf serum. Jurkat T cells were transiently transfected by a DEAE-dextran method with an SRE-Luc reporter plasmid as described (26). 24 h after transfection, cells were incubated without or with NEMO-derived peptides for 2 h and then mock-stimulated or stimulated with 100 ng/ml phorbol 12-myristate 13-acetate and 1 g/ml ionomycin for 5 h. Luciferase expression was carried out as described in Ref.…”
Section: Cell Lines Stable and Transient Transfections And Conditiomentioning
confidence: 99%
“…FACS Analysis-Stable cell lines (70Z/3-C3) were obtained after electroporation of 70Z/3 cells (26) in the presence of a cx12lacZ-B plasmid containing three tandem copies of an NF-B-binding site in the interleukin-2 promoter (27) upstream from the lacZ reporter gene (a gift from G. R. Crabtree). The human retinoblastoma cell line Y79 (American Type Culture Collection; Manassas, VA), was grown in RPMI 1640 medium supplemented with 100 units/ml penicillin, 100 g/ml streptomycin, and 10% fetal calf serum.…”
Section: Cell Lines Stable and Transient Transfections And Conditiomentioning
confidence: 99%
“…A more suitable ROI messenger would be the less reactive H 2 O 2 . However, arguments against ROI involvement in NF-B activation have been published (30 -32), and despite the fact that phorbol 12-myristate 13-acetate-dependent NF-B stimulation is cancelled by antioxidants, it has been recently shown that phorbol 12-myristate 13-acetate does not increase intracellular ROI (33). Peroxide-mediated stimulation of NF-B appears to be cell line-specific, since N-acetylcysteine, an antioxidant, elicited up-regulation of NF-B binding activity in monocyte-derived macrophages (34).…”
mentioning
confidence: 99%